KAJIAN HUKUM TENTANG KEPEMILIKAN SILANG SAHAM MENURUT UNDANG-UNDANG PERSEROAN TERBATAS NOMOR 40 TAHUN 2007 - , Furkano Farhan Juskal, SH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In the Law No. 40 Year 2007, Article 36 mentioned explanation about crossownership ban that occurs when the Company has issued shares by another company whose shares are directly or indirectly owned by the Company. Cross-ownership in the context of the issuance of new shares by the Company Law of the capital led to the company is clear there is no payment of capital in real terms into the management side of the company is, the cross-ownership is likely to lead to mixing between ownership and management of the company, so in this case management to be no longer independent of one against the other. The result is that the two or more companies will integrate with each other under the same ownership and management, horizontal integration and caused reduced competition, vertical integration led to the company's ability to set prices and conglomerate integration of macro-economic impact on small businesses caused by the reduced of competition. The same thing occurs in Act 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, it's just that the difference lies in the scale of the impact of cross-ownership (large or small).